Adherence to Antihypertensive Therapy: A Systematic Review of Russian Prospective Studies from 2000 to 2019 - E. V. Bochkareva; E. K. Butina; I. V. Kim; A. V. Kontsevaya; O. M. Drapkina (Столичная издательская компания, 2020)
Russia belongs to countries with a high prevalence of arterial hypertension (AH), which is the main cause of premature death in the Russian population. The level of blood pressure (BP) is controlled in less than a third of patients, which may be due to poor adherence to medical recommendations and irregular medication. The manuscript provides a review of studies evaluating the effectiveness of measures to improve adherence to antihypertensive therapy (AHT).Aim. To prepare a systematic review of Russian studies to assess the effectiveness of measures to increase adherence to AHT, to determine/describe the main directions of the intervention and the methodological level.Material and methods. The search for full-text articles on adherence to AHT published in Russian in the period from 2000 to 2019 was carried out in the main Russian and international electronic databases eLIBRARY.ru, Embase, Russian Medicine, MEDLINE. Of the 563 publications found, 20 were included in the review.Results. In 14 studies, adherence was assessed using the 4-item Morisky Medication Adherence Scale (MMAS-4), other studies used bespoke questionnaires or pill counts. Two studies examined factors associated with adherence. The observation period was up 6 weeks to 12 months, the number of participants is 30-2435 people. A higher adherence was noted in women, people over 50 years old, with higher education, working, with concomitant diabetes mellitus and a history of myocardial infarction. Patient education was effective interventions to improve adherence (in particular, in studies, improvement on the MMAS-4 from 1.8 to 3.9 points, p=0.0002 or from 2.80 to 3.79 points, p<0.0001), telephone reminders (p<0.0001), training in self-measurement of blood pressure (p<0.05) and fixed combinations of drugs (p<0.05).Conclusion. The most effective ways to improve adherence are patient education and the use of drugs fixed combinations. In most studies, subjective methods of adherence assessing were used.